Implementasi Kebijakan Pengelolaan Sampah Melalui Program Bank Sampah Induk Surabaya (Studi Di Bank Sampah Unit Kelurahan Ngagelrejo, Kecamatan Wonokromo, Kota Surabaya) - Noviyanti Noviyanti; Hesti Inggrit Noviani; Sovianti Octaviasari; Noor Kemalia; Fahmi Bargoyah; Deevana Baihaqy; Putri Septiani Zulfa (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
Improper waste management has the potential to cause disease, slum settlements, and natural disasters. Ngagelrejo Village, Wonokromo District, Surabaya City established a waste bank based on Regional Regulation of Surabaya City No. 1 of 2019 concerning Amendments to Regional Regulation of Surabaya City No. 5 of 2014 concerning Waste Management and Cleanliness in the City of Surabaya as an effort to implement waste management policies. This study aims to describe the implementation of waste management policies through Bank Sampah Induk Surabaya (BSIS). This type of research is descriptive research with a qualitative approach, which focuses on George Edward III's theory with indicators including: communication, resources, disposition, and bureaucratic structure. Resources have been fulfilled with the intervention of the foundation. The disposition has gone well starting from the appointment of executors and the provision of incentives. The organizational structure has been contained in the SOP compiled by the Bina Bhakti Environmental Foundation and under the guidance of PT. PLN (Persero).